Residential Proximity to Naturally Occurring Asbestos and Mesothelioma Risk in California - Pan, Xue-lei (American Thoracic Society, 2005)
Rationale: Little is known about environmental exposure to low levels of naturally occurring asbestos (NOA) and malignant mesothelioma (MM) risk. Objectives: To conduct a cancer registry-based case control study of residential proximity to NOA with MM in California. Methods: Incident MM cases (n = 2,908) aged 35 yr or more, diagnosed between 1988 and 1997, were selected from the California Cancer Registry and frequency matched to control subjects with pancreatic cancer (n = 2,908) by 5-yr age group and sex. Control subjects were selected by stratified random sampling from 28,123 incident pancreatic cancers in the same time period. We located 93.7% of subjects at the house or street level at initial diagnosis. Individual occupational exposure to asbestos was derived from the longest held occupation, available for 74% of MM cases and 63% of pancreatic cancers. Occupational exposure to asbestos was determined by a priori classification and confirmed by association with mesothelioma. Main Results: The adjusted odds ratios and 95% confidence interval for low, medium, and high probabilities of occupational exposures to asbestos were 1.71 (1.32–2.21), 2.51 (1.91–3.30), and 14.94 (8.37–26.67), respectively. Logistic regression analysis from a subset of 1,133 mesothelioma cases and 890 control subjects with pancreatic cancer showed that the odds of mesothelioma decreased approximately 6.3% for every 10 km farther from the nearest asbestos source, an odds ratio of 0.937 (95% confidence interval = 0.895–0.982), adjusted for age, sex, and occupational exposure to asbestos. Conclusions: These data support the hypothesis that residential proximity to NOA is significantly associated with increased risk of MM in California.